PENGARUH ROTASI KANTOR AKUNTAN PUBLIK (KAP), TENURE AUDIT DAN UKURAN KAP TERHADAP KUALITAS AUDIT - Faisal, Muhammad (JURNAL FAIRNESS, 2019)
Accounting is a form of accountability and conveying financial information of a company or organization to parties concerned. However, the accounting report could potentially be affected by private interests, while the users of financial reports are very concerned to receive reliable financial reports. Therefore there is a need for an independent third party to mediate the two parties (agent and principal) with different interests. The independent party is an auditor who is responsible to provide assessment and opinion statement on the fairness of the financial report presented. DeAngelo (1981) defines audit quality as "the probability of an auditor is able to find and report irregularity in client's accounting system”.This study aimed to empirically examine the effect of rotation of the public accounting firms, audit tenure, and the size of the public accounting firms on audit quality. The population of the data is the entire manufacturing companies listed on the Indonesia Stock Exchange in the period 2011 to 2016.This study used purposive sampling method to select sample from the population. Based on this method, sample of 51 manufacturing firms were obtained from the period 2011-2016. The multiple linear regression was used to analysis data. Proxy measurements for audit quality is using discretionary accrual Kazsnik model (1999).The results of multiple regression analysis show that the size of public accounting firm positivly affecting on audit quality while the rotation of the public accounting firms and audit tenure has no effect on audit quality.